“If I can get my work done, I’m not addicted to my phone”: Investigating smartphone use among language students - Qian Wang; Kizito Tekwa (PLoS ONE, 2026)
The study of smartphone addiction among college students reveals significant gaps, particularly in understanding its impact on specific academic groups, such as language learners, whose unique reliance on mobile applications (MAs) for learning remains underexplored. Existing research, often limited by cross-sectional designs and self-reported data, lacks context-specific insights into sociocultural factors and personality influences. This study addresses these lacunae by examining MA usage among 31 third-year English majors at a Chinese university perceived to be addicted based on the Smartphone Addiction Scale-Short Version (SAS-SV). The purpose was to investigate usage patterns, their correlation with academic performance and personality traits, and whether high usage amounted to perceived addiction within this cohort. A mixed-methods approach was employed, using 2 weeks of objective app-tracking data, a 50-item personality questionnaire, academic performance metrics, and qualitative reflections on usage motivations. Findings revealed 150,551 minutes spent on top MAs (WeChat, Xiaohongshu, Douyin), with 83.9% denying addiction despite high use, while 16.1% admitted compulsive behaviors affecting sleep and academics. Conscientiousness negatively correlated with usage time. No other correlations were found. Qualitatively, students cited communication, study, and entertainment as key drivers. Implications suggest reframing addiction as “high but largely functional smartphone engagement,” while advocating for policies to curb compulsive usage identified in 16.1% of participants. Universities should implement usage guidelines and provide counseling to foster a balanced digital environment.